Reziliencia a magyar oktatási rendszerben és longitudinális program adatainak tükrében - Tóth, Edit; Fejes, József Balázs; Patai, Jolán; Csapó, Benő (Magyar Pedagógia, 2016)
Although the Hungarian education system is not effective in compensating for disadvantages, the issue of academic resilience has not been addressed in Hungary.The aim of the present study is (a) to investigateresilience in Hungary by examining the level of resilience, the school careersof resilient studentsandthe waysresilience changes over time, as well as (b) to identifythe impact of some background variables. We analyzed the data forthe 2003–2011 cohort (N=4322) inthe Hungarian Longitudinal Program based on the results from themathematics, reading comprehension, inductive reasoning and science tests. We followed the PISA methodology in defining the concept of educational resilienceand identifying resilient students.The results show that the proportion of resilient students differs to a great extent among the domains examined. The role of school in compensating for disadvantages is the most influential in reading comprehension. There is no great difference in the proportion of resilient students in the domains among the age groups examined;however, the population of resilient students in the different domains varies to a great extent. From those defined as resilient at the start ofschool, only about 50% werecategorized as resilient in reading and science and 40% were classified as such in mathematics at the end of primary school. According to a cluster analysis,two resilient profile types were identified. Considerable differenceswere detected between the two profiles in maths(7.0–20.8%) and inductive reasoning (4.0–9.0%) tests. Girls are at an advantage in reading comprehension among disadvantaged students in all age groups;however, in other domains no differences could be identified in terms of gender. In general, the difference between rural and urban regions was not significant in most of the domains, while the proportion of resilient students in Budapestwas generally much higher than in other parts of the country.